Theoretical analysis of the mechanical behavior of double-ring joints under pure bending, bending-shear and eccentric loading conditions. (1st April 2021) - Zhang, Zhijie; Feng, Ruoqiang; Chen, Yao
Highlights: The model of double-ring joint was established under different loading conditions. The calculation formulas of the semi-rigid properties were derived. The formulas were verified by experimental and finite element analysis results. The hysteretic behaviors under cyclic load were analyzed by ABAQUS. Abstract: Taking double-ring joint as research object, the mechanical performances under pure bending, bending-shear and eccentric loading conditions of the joints were studied in this paper. Double-ring joints with different structural parameters were analyzed using finite element analysis and theoretical derivation methods and combined with experimental results. The following conclusions were obtained: 1) under the pure bending condition, the spring model of the double-ring joint was established, and the theoretical calculation formulas of the ultimate bearing capacity and initial rotational stiffness were derived; 2) under the bending-shear condition, the accuracy of finite element analysis models was verified by comparing the numerical with experimental results. The mechanical properties of double-ring joints under the bending-shear condition were similar to those under the pure bending condition; 3) based on the full-section plasticity criterion, the relationship between ultimate bending moment ratio η 0 N and axial force eccentricity δ was derived. With the exponential function for nonlinear fitting, the relationship between initial rotational stiffness ratio ξ 0 N and axial force eccentricity δ was derived.